An application of control charts in manufacturing industry - Muhammad Riaz; Faqir Muhammad (Journal of Statistical and Econometric Methods, 2012)
The range control chart and the X bar control chart are the well known and the most popular tools for detecting out- of-control signals in the Statistical Quality Control (SQC). The control charts has shown his worth in the manufacturing industry. In this study we have applied the range and the X bar control charts to a product of Swat Pharmaceutical Company. The variables under study were weight/ml, Ph, Citrate % and the amount of fill. Besides the X bar control chart, the exponentially weighted moving average control chart and the multivariate Hotelling's T2 control chart were applied to the same data.
Keywords: 330; descriptive statistics; data smoothing; estimation and detection mean